PENGEMBANGAN MEDIA REKTISANMORI PADA MATERI PESAN MORAL CERITA NARASI DI KELAS V - Wulan Sari, Rini; Djuanda, Dadan; Dwija Iswara, Prana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop REKTISANMORI (Automatic Correction of Moral Messages) media based on a website of moral message material for narrative stories to help students conclude moral messages in a narrative story. Based on the results of the research, the development of REKTISANMORI (Automatic Correction of Moral Messages) media based on a website of moral message material for narrative stories can be used in the learning process with the category of "very feasible" based on the results of the percentage of material experts and language experts of 91.66% and for media experts of 93.75%, as well as student response questionnaires with a percentage of 88.14%.